Non-horizontally Suspended Cable Dynamics with Flexible Tower Modulations - Guo, Tie-Ding; Wang, Lian-Hua; Kang, Hou-Jun; Zhao, Yue-Yu (Journal of Vibration Testing and System Dynamics, 2026)
Based upon an asymptotically reduced coupled model, nonlinear forced vibrations of a non-horizontally suspended cable is investigated in this paper, which is coupled with a ﬂexible oscillating tower. The cable’s nonlinear coupled dynamics is a modulated version of cable’s uncoupled dynamics, i.e., the cable dynamics with ﬁxed rigid towers. Nonlinear frequency responses of the cable-tower coupled system are found, with saddle-node bifurcations, Hopf bifurcations, and quasi-periodic behaviors detected. Special attentions are paid to the dynamic eﬀects caused by cable-tower coupling, boundary damping, and the inclinations.